Typhoon- and pollution-driven enhancement of reactive bromine in the mid-latitude marine boundary layer - Wang, Shanshan (2024)
Tropospheric reactive bromine is important for atmospheric chemistry, regional air pollution, and global climate. Previous studies have reported measurements of atmospheric reactive bromine species in different environments, and proposed their main sources, e.g. sea-salt aerosol (SSA), oceanic biogenic activity, polar snow/ice, and volcanoes. Typhoons and other strong cyclonic activities (e.g. hurricanes) induce abrupt changes in different earth system processes, causing widespread destructive effects. However, the role of typhoons in regulating reactive bromine abundance and sources remains unexplored. Here, we report field observations of bromine oxide (BrO), a critical indicator of reactive bromine, on the Huaniao Island (HNI) in the East China Sea in July 2018. We observed high levels of BrO below 500 m with a daytime average of 9.7 ± 4.2 pptv and a peak value of ∼26 pptv under the influence of a typhoon. Our field measurements, supported by model simulations, suggest that the typhoon-induced drastic increase in wind speed amplifies the emission of SSA, significantly enhancing the activation of reactive bromine from SSA debromination. We also detected enhanced BrO mixing ratios under high NOx conditions (ppbv level) suggesting a potential pollution-induced mechanism of bromine release from SSA. Such elevated levels of atmospheric bromine noticeably increase ozone destruction by as much as ∼40% across the East China Sea. Considering the high frequency of cyclonic activity in the northern hemisphere, reactive bromine chemistry is expected to play a more important role than previously thought in affecting coastal air quality and atmospheric oxidation capacity. We suggest that models need to consider the hitherto overlooked typhoon- and pollution-mediated increase in reactive bromine levels when assessing the synergic effects of cyclonic activities on the earth system.